No End In Sight: How regimes form barriers to addressing the wicked problem of displacement. Issue 10 (October 2022) - Frey-Heger, Corinna; Gatzweiler, Marian Konstantin; Hinings, C.R. (Bob)
Wicked problems are complex and dispersed challenges that go beyond the capacity of individual organizations and require a response by multiple actors, often in the form of transnational regimes. While research on regimes has provided insights into such collective responses, less is known about how such regimes may form barriers that hinder and block appropriate responses to addressing wicked problems. Exploring the problematic role of regime-level responses is timely given that many of today's wicked problems are far from being alleviated and in many instances appear instead to be intensifying. We draw from complementary insights of regime theory and research on institutional barriers to explore our research question: How do regimes form barriers to addressing wicked problems, and which mechanisms sustain such barriers? We explore this question with a longitudinal case study of the transnational regime for refugee protection and its response to displacement in Rwanda. From our findings, we develop a model of dissociation that explains how actors move further away from addressing a wicked problem. We identify four dissociative mechanisms (discounting, delimiting, separating, and displaying) that each create a distinct regime-level barrier. These barriers are distributed and mutually reinforcing, which makes it increasingly hard for actors to find alternative ways of responding to an escalating problem. Our study provides insights for research on regimes and wicked problems as well as studies on institutional barriers. We conclude with policy implications for overcoming those barriers, in line with the wider concerns and motivations of this special issue.